Matrix stiffness and oxigen tension modulate epigenetic conversion of mouse dermal fibroblasts into insulin producing cells. (International Journal of Health, Animal Science and Food Safety, 2017)
In vivo, cells are surrounded by a three-dimensional (3-D) organization of supporting matrix, neighboring cells and a gradient of chemical and mechanical signals (Antoni, et al., 2015). However, the present understanding of many biological processes is mainly based on two-dimensional (2-D) systems that typically provides a static environment. In the present study, we tested two different 3-D culture systems and apply them to the epigenetic conversion of mouse dermal fibroblasts into insulin producing-cells (Pennarossa, et al., 2013; Brevini, et al., 2015), combining also the use of two oxygen tensions. In particular, cells were differentiated using the Polytetrafluoroethylene micro-bioreactor (PTFE) and the Polyacrylamide (PAA) gels with different stiffness (1 kPa; 4 kPa), maintained either in the standard 20% or in the more physiological 5% oxygen tensions. Standard differentiation performed on plastic substrates was assessed as a control. Cell morphology (Fig.1A), insulin expression and release were analyzed to evaluate the role of both stiffness and oxygen tension in the process. The results obtained showed that 1 kPa PAA gel and PTFE system induced a significantly higher insulin expression and release than plastic and 4 kPa PAA gel, especially in low oxygen condition (Fig.1B). Furthermore, comparing the efficiency of the two systems tested, 1 kPa PAA gel ensured a higher insulin transcription than PTFE (Fig.1C). Recent studies show the direct influence of substrates on lineage commitment and cell differentiation (Engler, et al., 2006; Evans, et al., 2009). The evidence here presented confirm that the use of an appropriate stiffness (similar to the pancreatic tissue), combined with a physiological oxygen tension, promote β-cell differentiation, with beneficial effects on cell functional activity and insulin release. The present results highlight the importance of 3-D cell rearrangement and oxigen tension to promote in vitro epigenetic conversion of mouse fibroblasts into insulin-producing cells.
Keywords: epigenetic conversion; pancreatic differentiation; matrices; 3-D culture systems; oxygen tension.